Pengawasan Pasca Adopsi dalam Perspektif Perlindungan Anak: Studi Perbandingan Hukum Indonesia dan Australia - Cindy Marito Sihombing (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
Post-adoption supervision is a crucial aspect of ensuring the protection of children's rights after the formal legal adoption process. This study compares post-adoption supervision systems in Indonesia and Australia using a normative legal approach with a comparative method. In Indonesia, supervision is regulated by Law No. 35 of 2014 on Child Protection and Government Regulation No. 54 of 2007, but implementation frequently faces challenges such as low compliance with reporting obligations and limited psychosocial support services. In contrast, Australia has a more structured and comprehensive system through the Intercountry Adoptee and Family Support Service (ICAFSS), offering counseling, mediation, and strict supervision based on the open adoption principle. This study found that differences in legal culture and approaches to biological family involvement between the two countries significantly contribute to the effectiveness of post-adoption supervision. Recommendations for improving Indonesia's system include strengthening the legal framework, increasing the budget, and developing human resource capacity.